Regulatory measures affecting service trade and investment: Information and communications technology (ICT) services - Lai-Lynn Angelica B. Barcenas; Ramonette B. Serafica (Philippine Institute for Development Studies (PIDS), 2019)
Information and Communications Technology (ICT) infrastructure and services are necessary to spur economic growth especially in the digital age. The comparative advantage enjoyed by the Philippines in specific ICT and ICT-enabled services indicate the availability of competitive ICT to support services exports. ICT connectivity throughout the country needs to be significantly improved, however. Trade and investment in the sector must be further encouraged by creating an efficient regulatory framework to support sector development. In addition to market access restrictions, which will require amending the Constitution and other relevant laws, this review identified other critical issues. Priorities for reform that need to be addressed include improving transparency in legislative and regulatory procedures and requirements, establishing a mechanism to enforce competitive safeguards, strengthening the independence of the regulator, and better coordination among government agencies on ICT-related policies and programs.
Keywords: 330; Information and Communications Technology; digital; trade; investment; services; regulation; barriers; free trade agreements